Being Sherlock Holmes: Can we sense empathy from a brief sample of behaviour? - Wu, Wenjie; Sheppard, Elizabeth; Mitchell, Peter (Wiley, 2015)
Mentalizing (otherwise known as ‘theory of mind’) involves a special process that is adapted for predicting and explaining the behaviour of others (targets) based on inferences about targets’ beliefs and character. This research investigated how well participants made inferences about an especially apposite aspect of character, empathy. Participants were invited to make inferences of self-rated empathy after watching or listening to an unfamiliar target for a few seconds telling a scripted joke (or answering questions about him/herself or reading aloud a paragraph of promotional material). Across three studies, participants were good at identifying targets with low and high self-rated empathy but not good at identifying those who are average. Such inferences, especially of high self-rated empathy, seemed to be based mainly on clues in the target's behaviour, presented either in a video, a still photograph or in an audio track. However, participants were not as effective in guessing which targets had low or average self-rated empathy from a still photograph showing a neutral pose or from an audio track. We conclude with discussion of the scope and the adaptive value of this inferential ability.